Derechos de la naturaleza en Colombia: dispositivos e instrumentos de gestión ambiental de la administración pública desde una perspectiva de innovación - Álvarez-Rondón, Cristian Camilo (DIXI, 2025)
The contemporary environmental crisis poses a significant challenge to environmental law, which has historically been influenced by neoliberalism and an anthropocentric approach. This paper addresses the problem of the ineffectiveness of current legal instruments and devices in protecting the environment and materializing the rights of nature in Colombia. The research highlights how, despite regulatory and jurisprudential advances, the practical application of these rights faces serious limitations. Additionally, it was identified that environmental management mechanisms, although robust in their theoretical construction, are insufficient to address critical problems such as deforestation, pollution, and loss of biodiversity. Likewise, the weakness of the specific legislative framework to guarantee the rights of nature was observed, limiting its effectiveness. The article proposes the incorporation of information and communication technologies (ICT) to improve current environmental management, thus facilitating informed decision-making, surveillance, and monitoring of ecosystems. It was concluded that it is essential to transform the relationships between the State, communities, and the environment-subject, promoting the biocentric paradigm that recognizes the interdependence between human beings and nature. This work aims to contribute to the debate on the need to reform environmental law in Colombia to make it more effective in protecting the environment and promoting sustainable development that respects rights in their entirety. To do so, a qualitative methodology is adopted, with an analytical-critical approach that combines the analysis of the evolution of environmental law, the review of judicial rulings, and the study of existing environmental management instruments.